Biodegradation of Palm Kernel Cake with Multienzyme Complexes from Fungi and its Feeding Value for Broilers - Lawal, T.E.; Iyayi, E.A.; Adeniyi, B.A.; Adaramoye, O.A. (International Journal of Poultry Science, 2010)
Palm Kernel Cake (PKC) was used as a substrate to elicit the production of polysaccharidases from Aspergillus niger, Trichoderma viride, Rhizopus stolonifer and Mucor mucedo. The extracted enzymes produced were purified and used to ferment PKC in solid state at the rate of 250 ml/kg of the material for 7 days. Unbiodegraded and enzyme degraded PKC were used to formulate broiler starter and finisher diets at the rates of 70 g kg-1 and 100 g kg-1, respectively. A 6th diet was formulated in which Roxazyme G2G, a commercial enzyme was used to supplement the unbiodegraded PKC at the recommended inclusion level of 0.15 g kg-1. A total of 360 1-d-old broiler chicks were randomly allocated to the 6 treatments of 6 replicates each with each replicates having 10 birds. Cellulose and hemicellulose were significantly (p<0.05) reduced in the biodegraded PKC compared with the unbiodegraded PKC and PKC supplemented with Roxazyme G2G. The level of soluble sugars increased in a similar trend. Crude protein, phosphorus and energy increased significantly (p<0.05) in the biodegraded PKC compared to that treated with Roxazyme G2G and the unbiodegraded PKC. Apparent digestibility of nutrients was significantly improved (p<0.05) in birds that received the diets based on the biodegraded PKC than those on the unbiodegraded PKC and Roxazyme G2G supplemented diets. Feed conversion and weight gain in birds were significantly (p<0.05) higher in birds on the diets based on the biodegraded PKC compared to those on diets based on the unbiodegraded PKC and Roxazyme supplemented diets. Results of the study showed that PKC can act as a substrate for the production of a multienzyme complex from the 4 fungi. The enzyme complexes so produced were more efficacious in breaking down the cellulose and hemicellulose in it compared to Roxazyme G2G which is an enzyme product specific for cereal-based diets.